The Mind of the Organization / Revised Edition - Heirs Ben; Pehrson Gordon (Harper & Row Publishers, 1982)
Preface, Introduction: A View from Japan, The Increasing Importance of Organizational Thinking, The Decision-Thinking Function of the Human Mind, Individual Decision-Making and the Mind's Four-Stage Thinking Process, The Neglect of the Mind's Thinking Process, The Mind of the Organization and the Decision-Thinking Process, A Systems Approach to the Problems of Organized Complexity and the Responsibilies of an Organization's Mind, Major Barriers to the Effective Functioning of the Organization's Mind, Dismantling the Barriers: A Question of Management Attitude, Operational Procedures for Improving the Effectiveness of the Organization's Mind, Conclusion, Appendices, Ackwoledgements.
Preface, Introduction: A View from Japan, The Increasing Importance of Organizational Thinking, The Decision-Thinking Function of the Human Mind, Individual Decision-Making and the Mind's Four-Stage Thinking Process, The Neglect of the Mind's Thinking Process, The Mind of the Organization and the Decision-Thinking Process, A Systems Approach to the Problems of Organized Complexity and the Responsibilies of an Organization's Mind, Major Barriers to the Effective Functioning of the Organization's Mind, Dismantling the Barriers: A Question of Management Attitude, Operational Procedures for Improving the Effectiveness of the Organization's Mind, Conclusion, Appendices, Ackwoledgements.